2014
DOI: 10.1186/1471-2253-14-43
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative hypoxemia is common with horizontal positioning during general anesthesia and is associated with major adverse outcomes: a retrospective study of consecutive patients

Abstract: BackgroundReported perioperative pulmonary aspiration (POPA) rates have substantial variation. Perioperative hypoxemia (POH), a manifestation of POPA, has been infrequently studied beyond the PACU, for patients undergoing a diverse array of surgical procedures.MethodsConsecutive adult patients with ASA I-IV and pre-operative pulmonary stability who underwent a surgical procedure requiring general anesthesia were investigated. Using pulse oximetry, POH was documented in the operating room and during the 48 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 61 publications
1
25
0
1
Order By: Relevance
“…In a previous work, we reported that the perioperative hypoxemia rate was substantial in all operative procedure categories (Dunham et al 2014 ). Although the primary body position during the operative procedure was supine or lithotomy, the standard anesthesia practice was to maintain horizontal recumbency in all patients, except for a few in the sitting position.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In a previous work, we reported that the perioperative hypoxemia rate was substantial in all operative procedure categories (Dunham et al 2014 ). Although the primary body position during the operative procedure was supine or lithotomy, the standard anesthesia practice was to maintain horizontal recumbency in all patients, except for a few in the sitting position.…”
Section: Introductionmentioning
confidence: 84%
“…In 2014, our group published an investigation of patients who underwent extra-thoracic procedures under general anesthesia and had preoperative pulmonary stability (Dunham et al 2014 ). We provided evidence to suggest that the substantial rates of perioperative hypoxemia and perioperative pulmonary aspiration (POPA) may have been related to horizontal recumbency.…”
Section: Introductionmentioning
confidence: 99%
“…According to literature reports, potential risk factors include age, 6 obesity, 11 12 ASA classification, 10 12 OSAS, 13 14 operating time, 10 12 type of muscle relaxant, 15 16 and intraoperative position. 17 However, researchers reached different conclusions about these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxemia or low arterial blood oxygen tension is an unwanted physiological condition and can cause serious patient harm during general anesthesia and surgery (6). Hypoxemia is associated with cardiac arrest, cardiac arrhythmias, postoperative infections and wound healing impairments, decreased cognitive function and delirium, and cerebral ischemia through a number of metabolic pathways (7).…”
Section: Introductionmentioning
confidence: 99%